Organic selenium supplementation in layer hens and its transfer to the egg - Rodríguez-Alfaro, Marisol; Salas-Durán, Catalina; Orozco-Vidaorreta, Carlos (Agronomía Mesoamericana, 2019)
Introduction. Selenium is an essential trace mineral for human and animal health, is part of the selenoproteins, that have an antioxidant function, and also prevent and reduce the damage caused by free radicals in the organism. Objective. The objective was to evaluate the effect of the dietary supplementation with organic selenium in layer hens on the productive performance, egg quality and its transfer to the egg for human consumption. Materials and methods. Two trials were performed with flocks of 33 000 ISA Brown hens (of 32 and 40 weeks of age), in Alajuela province, Costa Rica, during the first semester of 2013. After a control period (four weeks), the diet was supplemented with 0.4 ppm of organic selenium (three weeks for adaptation and three weeks for enrichment), with a withdraw period (three weeks). Laying percentage, accumulated eggs, mortality, feed intake, egg weight and mass and feed conversion were monitored weekly; a sample of fifty birds per flock was used to evaluate body weight. Haugh units, shell thickness and yolk color were determined weekly in fifteen fresh eggs, fifteen seven days-old-eggs and fifteen fourteen-days-old eggs. The selenium concentration in eggs was measured in the three periods (six eggs per period). Results. No variations were observed on production performance parameters that can be attributable to the addition of the selenium. The dietary supplementation with organic selenium increased the egg content of this mineral, which varied from not being detected during the control period on both trials, to 0.14 µg/g and 0.39 µg/g during the supplementation period, respectively. The egg storage affected significantly (p<0.05) Haugh units and yolk color in both trials, and in trial 1 also affected egg weight and mass. Conclusion. Dietary supplementation of laying hens with organic selenium can lead to the production of added-value eggs.